The Protagonists and Ideas Behind the Personal Responsibility and Work Opportunity Reconciliation Act of 1996: The Enactment of a Conservative Welfare System - O'Connor, Brendon (Social justice, 2001)
The passage of the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 culminated over 20 years of conservative agitation against liberal welfare policies. The legislation demands self-sufficiency and personal responsibility, and the new welfare system can be viewed as a conservative social experiment with grand promises and possibly high social costs. Those concerned with poverty in America will have to closely monitor this new approach and find better ways of addressing poverty than they have in the past. Interviews with supporters and critics of the legislation are discussed.